Rotating Hydromagnetic Two-Fluid Convective Flow and Temperature Distribution in an Inclined Channel - Sri Ramachandra Murty, P.; Balaji Prakash, G.; Karuna Sree, Ch. (International Journal of Engineering and Technology, 2018)
Magnetohydrodynamic convective two-fluid flow and temperature distribution between two inclined parallel plates in which one fluid being electrically non-conducting and the other fluid is electrically conducting is studied. A constant magnetic field is applied normal to the flow. The system is rotated about y-axis with an angular velocity â€˜Wâ€™.Â Perturbation method is used to obtain solutions for primary velocity, secondary velocity and temperature distribution by assuming that the fluids in the two regions are incompressible, laminar, steady Â and Â fully Â developed. Â Increasing Â values Â of Â rotation Â is Â to Â reduce Â temperature Â distribution Â and Â primary Â velocity where as thesecondary velocity increases for smaller rotation, while for larger rotation it decreases.Â